Overview of Medication Administration to Hypertension Patients at Harapan Raya Community Health Center - Novia, Sinata; Tri, Daniarti; Nurul, Hidayah; Putri, Khairani; Rahmi, Rizki Asrina; Ranti, Juliati; Rapi, Sari Mayang (JUPE : Jurnal Pendidikan Mandala, 2024)
Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements with an interval of five minutes in a state of sufficient rest/calm. This research is a descriptive observational study. The research was conducted at Harapan Raya Community Health Center in April 2024. The sample in this study was hypertension patients who received treatment at Harapan Raya Community Health Center in March 2024. The instrument used in this research was secondary data from the monthly report of Harapan Raya Community Health Center in March 2024. The data used obtained and then analyzed by calculating the percentage of drug use. Based on the results at the Harapan Raya Community Health Center, it can be concluded that: Patients who consume a lot of hypertension medication are female with 75 respondents and 39 male respondents. The highest number of patients who took hypertension medication were in the elderly age range, with 68 respondents, 44 respondents for middle adults, and 2 respondents for early adults. The drug that is often used in community health centers is amlodipine 10 mg.